Laparoscopic vs open left hepatectomy for hepatolithiasis - Tu, Jin-Fu (The WJG Press and Baishideng, 2010)
AIM: To explore the feasibility and therapeutic effect of total laparoscopic left hepatectomy (LLH) for hepatolithiasis. METHODS: From June 2006 to October 2009, 61 consecutive patients with hepatolithiasis who met the inclusion criteria for LLH were treated in our institute. Of the 61 patients with hepatolithiasis, 28 underwent LLH (LLH group) and 33 underwent open left hepatectomy (OLH group). Clinical data including operation time, intraoperative blood loss, postoperative complication rate, postoperative hospital stay time, stone clearance and recurrence rate were retrospectively analyzed and compared between the two groups. RESULTS: LLH was successfully performed in 28 patients. The operation time of LLH group was longer than that of OLH group (158 ± 43 min vs 132 ± 39 min, P < 0.05) and the hospital stay time of LLH group was shorter than that of OLH group (6.8 ± 2.8 d vs 10.2 ± 3.4 d, P < 0.01). No difference was found in intraoperative blood loss (180 ± 56 mL vs 184 ± 50 mL), postoperative complication rate (14.2% vs 15.2%), and stone residual rate (intermediate rate 17.9% vs 12.1% and final rate 0% vs 0%) between the two groups. No perioperative death occurred in either group. Fifty-seven patients (93.4%) were followed up for 2-40 mo (mean 17 mo), including 27 in LLH group and 30 in OLH group. Stone recurrence occurred in 1 patient of each group. CONCLUSION: LLH for hepatolithiasis is feasible and safe in selected patients with an equal therapeutic effect to that of traditional open hepatectomy.